Roofed-Motorcycle How Relevant is the Concept for Malaysias Climate - Nasrul Azuan, Alang (Faculty of Mechanical & Automotive Engineering Technology, 2022)
By the end of the first quarter of 2020, almost every nation across the globe is shocked by the transmission of COVID 19 virus.